IMPROVING HISTORY LEARNING OUTCOMES THROUGH THE THINK PAIR AND SHARE TYPE COOPERATIVE LEARNING MODEL IN CLASS XI IPS 1 SMAN 2 MEDAN - Elsarah Natasha Br Sitepu; Muhammad Adika Nugraha; Sitti Aisyah (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to evaluate the effectiveness of the Think Pair and Share cooperative learning model in improving history learning outcomes in class XI IPS 1 SMA Negeri 2 Medan. The research method used was a pre-experiment with a one-group pretest-posttest design. The research sample consisted of 30 students randomly selected from class XI IPS 1. The instrument used was a test of history learning outcomes before and after the intervention. The data were analyzed using descriptive and inferential statistical techniques. The research results show a significant increase in history learning outcomes after implementing the Think Pair and Share cooperative learning model. These findings indicate that the model is effective in improving understanding and retention of historical material. The practical implication of this research is that a cooperative approach can be an effective alternative to improving history learning outcomes in high schools, especially at SMA Negeri 2 Medan. Future research can explore the influence of other factors that can influence the successful implementation of the cooperative learning model. Through collaboration between researchers, educators, and other stakeholders, continued efforts to integrate cooperative learning models into curricula and instructional practices can strengthen the positive impact of this approach. In this way, we can continue to improve the quality of history education and prepare students to become citizens who are skilled, critical, and knowledgeable about their history and cultural heritage.